2005
DOI: 10.1029/2005gl023434
|View full text |Cite
|
Sign up to set email alerts
|

Optical observations of meteoric dust in the middle atmosphere during Leonid activity in recent years 2001–2003 over India

Abstract: Twilight photometric technique has been used in order to demonstrate that the middle atmosphere can be perturbed by the presence of tiny particles delivered after an encounter with cometary dust trails like the one produced by 55P/Tempel‐Tuttle. The presence of meteoric dust in the atmosphere from the Leonid activity that occurred from 2001 to 2003 was detected by the twilight photometer operated at Pune (18.5°N, 73.9°E), India. The November 2001 and 2002 Leonid storms, and the 2003 November outburst, caused s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The comparison is found to be very good, and it is proved that the twilight technique provides qualitative information on the vertical distribution of aerosols. The comparative study showed that the screening height (discussed in section 5a) for the twilight technique is about 6 km, below which no direct information on atmospheric aerosols can be obtained [the validity of the technique has been explored by Padma Kumari et al (2004)]. The effective height h is computed by using h 0 ϭ 6 km in Eq.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The comparison is found to be very good, and it is proved that the twilight technique provides qualitative information on the vertical distribution of aerosols. The comparative study showed that the screening height (discussed in section 5a) for the twilight technique is about 6 km, below which no direct information on atmospheric aerosols can be obtained [the validity of the technique has been explored by Padma Kumari et al (2004)]. The effective height h is computed by using h 0 ϭ 6 km in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The most important circumstance, which gives an altitudinal sounding ability to the twilight event, is that only a comparatively thin layer of air above the earth's shadow contributes the maximum to the sky brightness at every given moment. The logarithmic gradient of twilight sky intensity at a fixed angle above the horizon where the earth's shadow traverses different layers of the atmosphere gives information about the vertical distribution of aerosols in the atmosphere (Bigg 1956(Bigg , 1964Volz and Goody 1962;Shah 1970;Jadhav and Londhe 1992;Nighut et al 1999;Mateshvili et al 2000;Padma Kumari et al 2003). This method is analogous to the method of rocket sounding.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently the modeling study carried out by Gunnar et al [2004] show that anthropogenic SO 2 emission is the major contributor to the stratospheric sulfate aerosol. Under extreme conditions of a meteor storm, such as the 2001 and 2002 Leonid activity, meteoric dust will also cause small‐scale, transient augmentations of the existing aerosol background [ Padma Kumari et al , 2005]. Since such events are predictable, they could be avoided when tracking other small‐scale variations.…”
Section: Introductionmentioning
confidence: 99%